Alterations in mitochondrial dynamics with age‐related Sirtuin1/Sirtuin3 deficiency impair cardiomyocyte contractility. Issue 7 (3rd July 2021) - Zhang, Jingwen; He, Zhibin; Fedorova, Julia; Logan, Cole; Bates, Lauryn; Davitt, Kayla; Le, Van; Murphy, Jiayuan; Li, Melissa; Wang, Mingyi; Lakatta, Edward G.; Ren, Di; et al.
Abstract: Sirtuin1 (SIRT1) and Sirtuin3 (SIRT3) protects cardiac function against ischemia/reperfusion (I/R) injury. Mitochondria are critical in response to myocardial I/R injury as disturbance of mitochondrial dynamics contributes to cardiac dysfunction. It is hypothesized that SIRT1 and SIRT3 are critical components to maintaining mitochondria homeostasis especially mitochondrial dynamics to exert cardioprotective actions under I/R stress. The results demonstrated that deficiency of SIRT1 and SIRT3 in aged (24–26 months) mice hearts led to the exacerbated cardiac dysfunction in terms of cardiac systolic dysfunction, cardiomyocytes contractile defection, and abnormal cardiomyocyte calcium flux during I/R stress. Moreover, the deletion of SIRT1 or SIRT3 in young (4–6 months) mice hearts impair cardiomyocyte contractility and shows aging‐like cardiac dysfunction upon I/R stress, indicating the crucial role of SIRT1 and SIRT3 in protecting myocardial contractility from I/R injury. The biochemical and seahorse analysis showed that the deficiency of SIRT1/SIRT3 leads to the inactivation of AMPK and alterations in mitochondrial oxidative phosphorylation (OXPHOS) that causes impaired mitochondrial respiration in response to I/R stress. Furthermore, the remodeling of the mitochondria network goes together with hypoxic stress, and mitochondria undergo the processes of fusion with the increasing elongated branches during hypoxia. The transmission electron microscope data showed that cardiac SIRT1/SIRT3 deficiency in aging alters mitochondrial morphology characterized by the impairment of mitochondria fusion under I/R stress. Thus, the age‐related deficiency of SIRT1/SIRT3 in the heart affects mitochondrial dynamics and respiration function that resulting in the impaired contractile function of cardiomyocytes in response to I/R. Abstract : Cardiac SIRT1 and SIRT3 are decreased with age. The age‐related SIRT1/SIRT3 deficiency causes impaired contractile function of cardiomyocytes due to mitochondrial dysfunction.